Bank capital buffers around the world: Cyclical patterns and the effect of market power - Carvallo Valencia, Oscar; Ortiz Bolaños, Alberto (Journal of Financial Stability, 2018)
We examine the effect of competition and business cycles on bank capital buffers around the world. We use a dataset of 3461 banks from 25 developed and 54 developing countries over the 2001–2013 period. Banks tend on average to exhibit pro-cyclical behavior. But capital buffers seem to be more pro-cyclical in developing countries. Our results show that more competition leads to higher buffers in developed countries but to lower buffers in developing ones. This evidence suggests that the “competition-stability” thesis adheres in developed economies, whereas “competition-fragility” makes more sense in developing countries. This asymmetric result may have important policy implications, particularly with regard to new, globally-negotiated capital adequacy standards.